New combinations in the fern genus Tectaria (Tectariaceae) for the Flora of China - Christenhusz, M. J. M. (Phytotaxa, 2014)
For studies on the fern family Tectariaceae for the Flora of China, four species previously treated as Ctenitopsis need new combinations in Tectaria. The new combinations are proposed here and information on their types is provided.